Penerapan Convergence Model dalam Penyusunan Kebijakan Petani Tambak Udang di Kawasan Pesisir Pantai Kabupaten Sumenep - Rahman, Sindi Arista; Syamsul, Syamsul; Fatmawati, Fatmawati; Zarnuji, Zarnuji; Santosa, Ribut (Universitas Galuh, 2025)
The application of the convergence model in formulating policies for structuring shrimp farmers in coastal areas aims to create unified perceptions, achieve consensus, and foster collaborative actions between the government and the community. This study employs a qualitative approach, conducting interviews with 10 informants, each asked 8 questions. The findings indicate that equal and open dialogue serves as a medium for both government and community engagement in a more humane and responsive policy convergence process. Active community participation in decision-making is a fundamental element in the convergence model, enabling policies to be more effective and accepted by the community. The alignment of perceptions within the convergence model represents an effort to harmonize understanding between the government and the community.